Acute and long-term results with the 3rd generation visually guided laser balloon ablation system for pv isolation - Funasako, Moritoshi; Petrů, Jan; Hála, Pavel; Janotka, Marek; Škoda, Jan; Chovanec, Milan; Šedivá, Lucie; Reddy, Vivek Y; Neužil, Petr (Journal of interventional cardiac electrophysiology, 2024)
BACKGROUND: Visually guided laser balloon ablation is known as an effective pulmonary vein (PV) isolation device. The third-generation laser balloon ablation system (X3) equipped with compliant balloon and an automated motor-driven laser output mechanism, namely RAPID mode, has been clinically proven for PV isolation. METHODS: PV isolation with X3 was performed in all the patients with paroxysmal and early-stage persistent atrial fibrillation (AF). Acute data for PV isolation and clinical outcomes including supraventricular tachyarrhythmia (SVT: AF, atrial flutter, or atrial tachycardia)-free survival rate beyond 1 year were analyzed. RESULTS: A total of 110 patients (62 ± 13 years old, 80% of paroxysmal AF) were treated with X3. RAPID mode with was utilized to achieve PV isolation in all cases. In combination with RAPID mode and spot mode laser ablation, 91.1% (380/417) of veins were isolated on the first circumferential lesion set and did not require touch-up ablation and during the index procedure 100% of attempted veins were isolated. The mean procedure time was 77.0 ± 22.7 min and LA dwell time was 61.9 ± 22.0 min. Total duration of laser application was 5.1 ± 2.3 min per vein. At 1 year, SVT-free survival rate was 93.7% in paroxysmal AF patients, and 81.1% in persistent AF patients. CONCLUSIONS: A novel continuous automatic laser balloon ablation system was proved to be safe and effective for both paroxysmal and persistent AF patients. The clinical result demonstrated that PV isolation with X3 could achieve a high SVT-free survival rate.
Keywords: Humans; laserová terapie; lidé středního věku; venae pulmonales; Pulmonary vein isolation; Aged; výsledek terapie; senioři; lidé; Atrial Fibrillation; Rapid mode; katetrizační ablace; Laser Therapy; Laser balloon; Middle Aged; Pulmonary Veins; Treatment Outcome; Catheter Ablation; Atrial fibrillation; fibrilace síní